THE ROLE OF THE CEFR CERTIFICATE IN TEACHING ENGLISH IN UZBEKISTAN - Boborahmatova, Oytula; Yugay , Evgeniya Viktorovna (INTERNATIONAL CONFERENCE DEDICATED TO THE ROLE AND IMPORTANCE OF INNOVATIVE EDUCATION IN THE 21ST CENTURY, 2022)
The Common European Framework of Reference (CEFR) is the most comprehensive, and the most widely used of foreign language education standards through the world. The recent reforms in foreign language teaching in Uzbekistan have mainly touched on teaching English language in all levels and stages of education. This article covers continuous education, methods of teaching language and some elements of assignment.